IN VITRO ASSOCIATION OF SEED BORNE FUNGI WITH PEA IN CENTRAL INDIA (Journal of Plant Disease Sciences, 2025)
Pea is a most important legume in several developing and developed countries including India. In the present investigation, keeping in view these facts, Seed samples were collected from four districts of Madhya Pradesh . Katni, Mandla, Narsinghpur and Jabalpur during 2018-19 for evaluation of associated fungi on pea seed. These sample studied for detection of seed mycoflora by Standard Blotter Paper Method recommended by ISTA. Atotal of six genera were identified and recorded from seeds of pea. During the surveyed years, the highest incidence of seed/seedling disease (53.0 and 32.4%) was recorded in Jabalpur, followed by Fusarium wilt (42.5 and 44.5%), powdery mildew (62.8 and 64.4%) and downymildew (22.2 and 16.4%). The result of the present studies provides the baselineinformation about seed mycoflora for further studies and management of seedborne diseases associated with pea seeds.
Keywords: Pisum Sativum Standard Blotter Paper Method, Seed borne fungi